2004
DOI: 10.1016/s1472-6483(10)61108-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment of intrauterine pathologies with office hysteroscopy in patients with recurrent IVF failure

Abstract: The study was conducted to evaluate if the diagnosis and treatment of intrauterine lesions with office hysteroscopy is of value in improving the pregnancy outcome in patients with recurrent in-vitro fertilization and embryo transfer failure. Four hundred and twenty-one patients who had undergone two or more failed IVF-embryo transfer cycles were prospectively randomized into two groups. Group I (n = 211) did not have office hysteroscopic evaluation, Group II (n = 210) had office hysteroscopy. The patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
138
0
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(159 citation statements)
references
References 28 publications
4
138
0
17
Order By: Relevance
“…It has been shown that the fertility-enhancing effect of oHS could also be independent from the correction of intrauterine abnormalities. Hysteroscopy has been proposed to improve ART outcomes through an endometrial injury process leading to embryo implantation (23,24). The outcomes of the women in the oHS arm without any pathologic findings being generally more favorable compared to those without oHS in our data is speculating this impact.…”
Section: Discussionmentioning
confidence: 54%
“…It has been shown that the fertility-enhancing effect of oHS could also be independent from the correction of intrauterine abnormalities. Hysteroscopy has been proposed to improve ART outcomes through an endometrial injury process leading to embryo implantation (23,24). The outcomes of the women in the oHS arm without any pathologic findings being generally more favorable compared to those without oHS in our data is speculating this impact.…”
Section: Discussionmentioning
confidence: 54%
“…Daha önce yapılan çalışma-larda bu oran %11-45 arasında bildirilmiştir. 3,4 Sonuçları hasta populasyonunun yaşı, hormonal durumları, etnik faktörler ve infertilite tipi de etkileyebilir. Çalışmaların çoğunda IVF öncesi ofis histeroskopi ile saptanmış olan anormal bulguların oranı verilmiş olmasına rağmen, bu patolojik bulguların tedavi edilmesi sonucunda fayda gören ve gebe kalan hastaların oranlarından bahsedilmemektedir.…”
Section: Discussionunclassified
“…2 Gözardı edilmemesi gereken, bu uterin kaynaklı patolojilerin sıklığının yapılan çalışma-larda %11-45 oranında bulunmasıdır. 3,4 Bu patolojilerin ekarte edilebilmesi için kavitenin çok iyi bir şekilde değerlendirilmesi gerekmektedir.…”
unclassified
“…In a prospective randomized study conducted with 415 IVF patients, it was concluded that polypectomy was effective and increased pregnancy rates compared to the control group (8). In another study of 215 infertile patients where polypectomy was performed before intrauterine insemination, it was concluded that polypectomy increased the pregnancy rate 2.1 times (9).…”
Section: Discussionmentioning
confidence: 99%